SELF MOTIVATION BELIEFS ON THE ACADEMIC SELF REGULATION OF ARABIC LEARNERS AT DARUL LUGHAH WAD DA’WAH BANGIL - Hunainah, Hunainah; Hasanah, Mamluatul; Sutaman, Sutaman; Setyawan, Cahya Edy; Nasarudin, Nasarudin (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Academic self-regulation plays a crucial role in mastering the fundamental Arabic language skills, focusing on planning, performance, and evaluation stages. Within academic self-regulation, self-motivation beliefs are vital during the planning phases. This qualitative case study conducted at Darul Lughah Wad Da'wah Islamic boarding school involved data collection through observation, interviews, and document analysis. The study aimed to uncover students' self-motivation beliefs in learning Arabic and identify the dominant form of these beliefs. The findings indicated that students' self-motivation beliefs include self-efficacy influenced by peers, goal orientation driven by personal and family expectations, religious values, and expectations related to working and studying abroad. Among these, religious values emerged as the primary motivator for students' academic self-regulation in learning Arabic at Darul Lughah Wad Da'wah. From the results of this research, it can be observed that the dominant factor during the 4 sub-processes of self-motivation beliefs among female students in the boarding school significantly enhances their speaking skills. This study provides essential insights to enhance independent Arabic speaking skills within the sub-processes of self-motivation beliefs, in a boarding school context.